Real-world maintainable software : ten coding guidelines in practice - Marín-Pérez, Abraham (O'Reilly Media, 2016)
The software development industry is increasingly realizing that success depends on a project's long-term viability. To help with that effort, the Software Improvement Group (SIG) has identified ten guidelines for delivering code that's easy to maintain and adapt over time. While a full examination of these guidelines is available in Building Maintainable Software (O'Reilly), this report focuses on their application in the real world. Author and agile consultant Abraham Marin-Perez briefly explores each guideline and uses a running example to demonstrate how they can work together in a production environment. You'll also get case studies of ten European organizations that have significantly benefitted from these guidelines. The Ten Guidelines for Maintainable Software aren't just a theoretical exercise. In fact, SIG created them after years of analyzing what made some software projects successful and maintainable, while many others ultimately fell short. By applying these guidelines, you'll benefit from the wisdom of developers who preceded you.